Kearifan lokal satu desa tiga aksi: cegah hipertensi, pola hidup sehat, dan pemanfaatan tanaman obat keluarga - Suprapti, Tuti; Mutiudi, Ade Iwan; Tambunan, Irisanna; Jundiah, Raden Siti; Mukaromah, Raihany Sholihatul (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Public health in Indonesia faces complex challenges, including a high prevalence of hypertension, suboptimal waste management, and low utilization of Family Medicinal Plants (FMP). Hypertension, as a non-communicable disease, requires education on healthy lifestyles, while wise waste management is crucial for preventing environmentally-related diseases. FMP offers promotive and preventive solutions based on local wisdom, but has not been optimally utilized in rural areas. In Cibeet Village, Bandung Regency, these three issues are interconnected and demonstrate the need for integrated, community-based interventions. The